Minimum Wages at a Turning Point? - Balázs Égert; Jarmila Botev; Dave Turner (CESifo GmbH, 2024)
This paper uses cross-country macroeconomic empirical evidence among OECD countries to examine possible non-linear effects on employment of raising the minimum wage, in particular that marginal disemployment effects become larger when the initial minimum wage is already high. Some evidence is found for such effects, particularly for female and older workers, although the estimated threshold beyond which this occurs – at roughly 50%-60% of the median wage – above which such effects become apparent should be viewed as indicative rather than precise point estimates. The paper also finds that these non-linear disemployment effects are much more apparent for countries with strict Employment Protection Legislation (EPL) and/or with a high labour tax wedge. This suggests caution in applying the findings from much of the 'new' minimum wage literature based on US evidence to other OECD countries where EPL and tax wedges are typically stricter/higher.
Keywords: J20; J30; 330; minimum wage; employment; EPL; tax wedge; female workers; older workers; youth workers.